2019
DOI: 10.1377/hlthaff.2018.05228
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Services Improve Access To Care, Preventive Services, And Satisfaction Among Health Center Patients

Abstract: Enabling services address a combination of social determinants of health and barriers to access to primary care and are intended to reduce health disparities. They include care coordination; health education; transportation; and assistance with obtaining food, shelter, and benefits. Empirical evidence of enabling services' potential contribution to health outcomes is limited, which impedes their widespread dissemination. We examined how the receipt of enabling services influenced patient health care outcomes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 22 publications
0
36
1
2
Order By: Relevance
“…Recent studies have shown a positive relationship between screening for and addressing HRSN and health care utilization, including cancer screening and treatment (82)(83)(84)(85). In addition, lower rate of colorectal cancer screen are observed in other educated AA populations elsewhere, which we did not observe in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Recent studies have shown a positive relationship between screening for and addressing HRSN and health care utilization, including cancer screening and treatment (82)(83)(84)(85). In addition, lower rate of colorectal cancer screen are observed in other educated AA populations elsewhere, which we did not observe in our study.…”
Section: Discussioncontrasting
confidence: 79%
“…Given the demonstrated and potential efficacy of these factors in improving health care provided by health centers, HRSA has invested hundreds of millions of dollars to accelerate and optimize the adoption of health information technology, as well as incentivize the adoption of the patient-centered medical home model of care through its Quality Improvement Awards [30] . While previous studies have found positive effects of these innovations on access to care, quality of care, and disparities [26] , [32] , [33] , additional analyses may examine their potential impact specifically on pediatric influenza vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several institutional factors which may contribute to health centersā€™ ability to provide equitable access to services across a broad range of clinical domains, such as cancer screening, chronic condition management, prenatal care, and well-visit check-ups. These institutional factors include the provision of supportive services (e.g., care coordination, health education, translation, transportation), early and widespread implementation of electronic health records, and recognition as patient-centered medical homes [26] , [32] , [33] . Strengthening access to and quality of primary care broadly through these efforts may translate to increased use of specific services including influenza vaccinations, and fewer missed opportunities for influenza vaccinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Federal statute governing the Health Center Program requires that CHCs offer a comprehensive set of services beyond primary care, such as behavioral, oral, pharmacy, and ā€œenablingā€ services that facilitate access to and better use of health care services (examples of these ā€œenablingā€ services often include transportation, case management, health education, and translation). Recent research demonstrates that enabling services help patients navigate the health care system and achieve greater access to needed care ( Yue et al, 2019 ) and may even lead to improved health outcomes, although more research is needed on specific patient outcomes.…”
Section: Discussionmentioning
confidence: 99%